Self-Regulated Learning and Technology Perception as Predictors of English Achievement in Islamic Higher Education - Muhammad, Sugiyanto; Sabat, Yuliyanto (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
Society's demand for technology use in education affects how students manage their learning, particularly in ELT. This study investigates the effects of SRL strategies and perceptions of technology on English achievement at Luqman Al-Hakim Islamic College. Adopting a quantitative methodology, the study employed survey data collected from 30 undergraduate students enrolled in a General English class using validated questionnaires on SRL strategies, technology perception, and English achievement. Multiple linear regression analysis was used to determine how much variance in students’ General English achievement could be explained by SRL strategies and perceptions of technology. The findings suggest that SRL strategies are a significant positive predictor of English achievement. Perceptions of technology also have a strong positive influence on General English achievement and contribute significantly to the explanatory power of the regression model. These results suggest that effective SRL and positive perceptions of technology play an important role in improving students’ English learning outcomes. The findings imply that teaching approaches focusing on SRL through educational technology may lead to better General English learning performance at Islamic universities.